KEBEBASAN BERKONTRAK DAN BATASANNYA: Analisis Dalam Perspektif Contract Drafting - Mochamad Novel; Michael Vernando Sirait; Natanael; Benedict Artika Sari Asmin; Elissa Virginia (Halu Oleo University, 2025)
The purpose of this research is to analyse the role of contract drafting in ensuring the implementation of the principle of freedom of contract while remaining in line with legal constraints, morality, and public order, in order to create valid, balanced contracts that provide legal certainty for the parties. This research uses a normative juridical method by examining relevant laws and regulations, doctrines, and court decisions. The analysis shows that freedom of contract from a contract drafting perspective must always be understood within the framework of a balance between autonomy of will and legal protection. Contracts drafted without considering legal constraints have the potential to give rise to disputes or even be deemed null and void. Therefore, innovation in contract drafting is needed to ensure contracts remain flexible for the parties while remaining within the applicable legal framework.